Life Adjustment of International Students in Eastern Taiwan - Suprapto, Nadi; Saragih, Orde Koria; Al Ardha, Muchamad Arif (Journal of International Students, 2019)
This study investigates international students' life adjustment in Eastern Taiwan by conducting a survey study. A total of 104 students were invited to complete the Life Adjustment Questionnaire (LAQ). Several predictors’ (gender, major differences, and study levels) were studied in this survey. The results revealed seven important points, including the validity and reliability of LAQ, the degree of adjustment, adjustment across gender, the correlations among dimensions of adjustment, adjustment across majors, adjustment across study levels, and the interaction among gender, major, and study level together concerning adjustment. The research gives some implications for further research and recommendations for universities related to international students.